Social media usage and organizational performance: Reflections of Malaysian social media managers - Parveen, F.; Jaafar, N.I.; Ainin, S. (Elsevier, 2015)
Social media usage among organizations is growing tremendously. Organizations are now building and maintaining social media public pages to improve their social network salience, enhance interest in their organizations, and build relationships with the online public. The majority of the studies on social media usage are based on the individual perspective while some are from the organizational perspective. However, not many studies have investigated the actual impact of social media usage on organizational performance. Therefore, using the qualitative approach, this study investigates the various purposes of social media usage and its impact on organizational performance. This study however, focuses only on the social media managers' views. The senior managers of six organizations that are using social media are interviewed from which we find that social media is used for various purposes in organizations, such as advertising and promotion, branding, information search, building customer relations and many more. The results also show that social media has a greater impact on the performance of organizations in terms of enhancement in customer relations and customer service activities, improvement in information accessibility and cost reduction in terms of marketing and customer service. (C) 2014 Elsevier Ltd. All rights reserved.